Features of science communication: implication of dialogism in an asynchonous interaction - Guilherme da Silva Lima; Marcelo Giordan (Investigações em Ensino de Ciências, 2017)
We present in this essay a theoretical reflection with aim of investigate the implications of the dialogism in case of asynchronous interactions in the scientific communication, when communicated by writing. In order to do so, we problematize the question of asynchrony and orient our analyzes in the concept of dialogism proposed by Bakhtin's circle. In our discussion we highlight two dimensions of the dialogism present in the interactions promoted by DC and in its statements, which we call speech-object and speech-response relationship. Finally, we present examples of interactions that occur through the section letters of the readers of Ciência Hoje magazine, as well as excerpts from two articles of DC, published by Ciência Hoje institute and by the G1, in which the anticipation of response is evident.